The Effects of Slow Stroke Back Massage and Lavender Aromatherapy on Blood Pressure in Hypertensive Patients - Sani, Fakhrudin Nasrul; Irdianty, Mellia Silvy (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Elderly is an age group which is extremely susceptible to suffer from health problems such as hypertension. Hypertension among the elderly is instigated by structural and functional changes in blood vessels. The changes include atherosclerosis, loss of connective tissue elasticity, and decreased vascular muscle relaxation that it reduces the distension and tensile strength of blood vessels. One of the therapies that may be implemented to elderly with hypertension is slow stroke back massage (SSBM) and lavender aromatherapy. The study aims to discover the effects of slow back massage (SSBM) and lavender aromatherapy toward the reduced blood pressure among hypertensive elderly.Subjects and Method: It was a quasi-experiment study with no control group which had been conducted in Posyandu (Integrated Health Post) Kamboja, Plesungan, Gondangerjo, Karanganyar, Central Java, in July 2019. A sample of 40 elderlies was selected by using total sampling. The dependent variables were systolic and diastolic blood pressure. The independent variables were slow stroke back mass-age (SSBM) and lavender aromatherapy. Blood pressure was measured by sphygmomanometer. The data were analyzed by using Wilcoxon. Results: The average systolic blood pressure post slow stroke back massage therapy and la-vender aroma therapy was (Mean=133.63; SD= 7.34) compared with prior therapy was (Mean= 167.80; SD= 6.12) with the value of p<0.001. The average diastolic blood pressure post slow stroke back massage therapy and lavender aroma therapy was (Mean= 68.28; SD= 4.25) compared with the prior therapy was (Mean= 68.88; SD= 5.72) with the value of p<0.001. Conclusion: Slow stroke back massage (SS-BM) lavender aromatherapy may lower down blood pressure of hypertensive elderly.Keywords: Hypertension, slow stroke back massage, Lavender aromatherapy, elderlyCorrespondence: Fakhrudin Nasrul Sani. School of Health Sciences Kusuma Husada, Surakarta. Email: fakhrudin_ns@ymail.com.Indonesian Journal of Medicine (2020), 05(03): 178-184https://doi.org/10.26911/theijmed.2020.05.03.01